2016
DOI: 10.1093/chromsci/bmw116
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Photochemically Induced Fluorescence Detection for HPLC Determination of Genotoxic Impurities in the Vortioxetine Manufacturing Process

Abstract: An analytical reversed-phase high-performance liquid chromatography (HPLC) method for the detection and quantitative determination of two genotoxic impurities at ppm level present in the vortioxetine manufacturing process is described. Applying the concept of threshold of toxicological concern, a limit of 75 ppm each for both genotoxic impurities was calculated based on the maximum daily dose of active pharmaceutical ingredients. The novel reversed-phase HPLC method with photochemically induced fluorescence de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…7). Therefore, aminosulfide and nitrosulfide impurities were confirmed as genotoxic, need to quantify by accurate, sensitive, and quantitative method such as RP-HPLC method in combination with PIF [25].…”
Section: Voriconazolementioning
confidence: 99%
“…7). Therefore, aminosulfide and nitrosulfide impurities were confirmed as genotoxic, need to quantify by accurate, sensitive, and quantitative method such as RP-HPLC method in combination with PIF [25].…”
Section: Voriconazolementioning
confidence: 99%
“…Soni and Sanjay developed an RP-HPLC method for the estimation of meloxicam and paracetamol with its GIs in bulk and combined dosage form using photodiode-array detection detector [15]. Dousa et al reported an RP-HPLC method for the analysis of GIs in the vortioxetine using a fluorescence detector [16].…”
Section: Hplcmentioning
confidence: 99%
“…These two last adsorbents can both be used in the pH range between 1 and 11. A wide number of published results in 24] and XSelect CSH C18 [25][26][27] can be found in literature. All three packings generally use alcohol:water or acetonitrile:water solvents, often with an acid or basic modifier (typically 0.1%).…”
Section: Introductionmentioning
confidence: 99%